Thermomechanical fatigue experiment and failure analysis on a nickel-based superalloy turbine blade. (August 2019) - Wang, R.; Zhang, B.; Hu, D.; Jiang, K.; Liu, H.; Mao, J.; Jing, F.; Hao, X.
Abstract: Thermomechanical fatigue (TMF) experiment with dwell times on a nickel-based superalloy turbine blade was conducted. The strain field and temperature field of the test section were simulated well through adjusting gripping fixture and induction coil. In addition to the loading, heating, cooling and control subsystems, high temperature strain measurement subsystem was introduced into the experiment to ensure the accuracy of the simulation results of service condition for the test section. In the whole experiment, the service condition of the test section was reproduced. The experiment result showed that TMF crack initiated at the trailing edge of the test section and propagated along the leading edge direction. Using the scanning electron microscope (SEM), multiple crack sources at the surface of turbine blade were observed and the crack surface was oxidized seriously. In addition, based on the fractographic and metallographic observation, the mixed features of intergranular fracture and transgranular fracture were found. The interaction of oxidation, creep damage and fatigue damage is an important reason for the TMF failure of the turbine blade. Highlights: The adjusting screw was introduced to change the interval of joints and obtain continuous stress values of test section. High temperature strain measurement subsystem was introduced to ensure the accuracy of the simulated loads in the lab. The fractographic sample with well-preserved crack surface was observed through the scanning electron microscope (SEM). The metallographic samples obtained from different positions were observed to investigate the damage mechanism of TMF.